A comparative study of shear stresses in collagen-GAG and calcium phosphate scaffolds in bone tissue-engineering bioreactors - KELLY, DANIEL (Mary Ann Liebert, 2008)
The increasing demand for bone grafts combined with their limited availability and potential risks has led to much new research in bone tissue engineering. Current strategies of bone tissue engineering commonly utilize cell-seeded scaffolds and flow perfusion bioreactors to stimulate the cells to produce bone tissue suitable for implantation into the patient?s body. The aim of this study was to quantify and compare the wall shear stresses in two bone tissue engineering scaffold types (collagen-GAG and calcium phosphate) exposed to fluid flow in a perfusion bioreactor. Based on ?CT images, 3D numerical CFD models of the two scaffold types were developed to calculate the wall shear stresses within the scaffolds. For a given flow rate (normalized by the crosssectional area of the scaffolds), shear stress is 2.8-fold higher in the collagen- GAG than the calcium-phosphate scaffold. This is due to the differences in scaffold geometry, particularly the pore size (collagen-GAG pore size ~96?m and calcium phosphate pore size ~350?m). The numerically obtained results were compared to an analytical method which is widely used by experimentalists to determine perfusion flow rates in bioreactors. Our CFD simulations revealed that the cells in both scaffold types are exposed to a wide range of wall shear stresses throughout the scaffolds, and that the analytical method predicts shear stresses 12% to 21% greater than those predicted by the CFD method. The study has demonstrated that the wall shear stresses in calcium phosphate scaffolds (745.2mPa) are approximately 40 times higher than in collagen-GAG scaffolds (19.4mPa) when flow rates are applied which have been experimentally used to stimulate the release of PGE2. These findings indicate the importance of using accurate computational models to estimate shear stress and determine experimental conditions in perfusion bioreactors for tissue engineering.
PUBLISHED
Keywords: Tissue Development and Growth; Fundamentals of Tissue